STUDY OF THE QUALITY OF LIFE OF PATIENTS WITH MENINGO-VASCULAR BRAIN TUMORS IN THE BEFORE AND POSTOPERATIVE PERIOD (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Meningiomas account for 13.0–36.6% of all known tumors affecting the central nervous system. system [1]. They occupy 2nd place in the composition of oncological processes occurring in the brain (GM) [1, 2]. They are characterized by manifestation in old age. In the group of histologically benign tumors, meningiomas are the leaders, making up up to 53.2%.